Opioides e violência no México: evolução e dimensões transnacionais contemporâneas - Barreto, Leonardo Luciano (2021)
Mexico has established itself as the main supplier of illicit opioid drugs to the US over the first two decades of the 21st century. By tracking connected processes and mechanisms in a chain of causality through the method of process tracing, this research aims to analyze the evolution of the opioid market in Mexico from a transnational perspective, comprising a complex network of articulated actors placed in licit and illicit markets in order to meet the demand of a broad consumer market in the United States of America, which has changed the dynamics of Mexican crime and violence. It was noted that this market responds to an external demand formed as a result of the overuse of prescription opioids since the late 1990s in the US. Capturing this demand with singular precision, Mexican criminal groups acted to structure a complex network permeated by continuous processes of violence and transnational flows and dynamics, involving a set of actors that move simultaneously between legal and illegal dimensions such as chemical and pharmaceutical corporations, health agencies, police and military forces and political leadership. Therefore, this research has sought to understand the structure of this market under two decisive moments: the expansion and consolidation of heroin as the most widely trafficked opioid until 2013 and the transition to the fentanyl market since then. It is concluded that this transition, more than the absorption of an external demand, is the result of a strategic calculation of Mexican criminal groups which aims to increase profitability and reduce operational risks through the trade of a powerful and profitable synthetic drug even in small quantities, besides not depending on poppy cultivation, a frequent target of crop eradication operations. Regarding the scenario of intensified violence that has built up over the last two decades, it was identified that the open competition for these markets among criminal groups, as well as the militarization of the so-called “war on drugs” are decisive factors to explain it, even though the relationship between the state and criminal groups has alternated between periods of convergence and antagonism